The importance of qualitative social science research for informed public health policy at local and national levels: insights from a local health district in New South Wales, Australia - Jennifer White; Jennifer White; Kirrilly Thompson; Kirrilly Thompson; Joanne Talwar; David N. Durrheim; David N. Durrheim (Frontiers in Public Health)
Australia employs an evidence-based approach to public health policy, emphasizing disease prevention, health promotion, and healthcare access that is informed by relevant research. However, implementing effective policy can be challenging due to the complexity of various public health issues. Social and behavioral factors significantly impact individual and community health outcomes, necessitating a deeper understanding of their interrelationships. Social science theories and methodologies provide critical insights into the complex relationships between individuals and society. This perspective paper highlights the critical role of qualitative social science research in shaping public policy by offering rich, contextual insights that quantitative data alone cannot capture. This article examines the benefit of incorporating qualitative social science research in a New South Wales (NSW) local health district’s pursuit of evidence-based approaches. Through five case studies, we demonstrate how qualitative social science research has been instrumental in addressing key public health challenges, particularly in managing zoonotic diseases and pandemics, ultimately informing and shaping public health policy.